2014
DOI: 10.1007/s00259-014-2714-x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor hypoxia and microscopic diffusion capacity in brain tumors: A comparison of 62Cu-Diacetyl-Bis (N4-Methylthiosemicarbazone) PET/CT and diffusion-weighted MR imaging

Abstract: Tumor hypoxia assessed by (62)Cu-ATSM PET/CT correlated with microscopic diffusion capacity obtained by DWI in brain tumors. Both (62)Cu-ATSM PET/CT and DWI were considered feasible imaging methods for grading glioma. However, (62)Cu-ATSM PET/CT provided additional diagnostic information to differentiate between GBM and PCNSL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
2
12
2
Order By: Relevance
“…SUVmax correlated positively with HIF–1a immunostaining Beppu et al [123]Intratumoural pO2 measured using microelectrodes during tumour resection and HIFa immunostaining correlated with FRP-170 uptake in 12 patients with high-grade gliomas. The mean pO2 was significantly lower in the areas of high uptake than in those of low uptake, suggesting that high accumulation of FRP-170 might indicate viable hypoxic tissuesCu-ATSM Hino-Shishikura et al [225]Tumour hypoxia assessed by [ 62 Cu]Cu-ATSM PET/CT correlates with diffusion capacity obtained by diffusion weighted MRI imaging and may be useful for grading gliomas. [62Cu]Cu-ATSM uptake was significantly higher in high-grade gliomas than in normal or lower grade tumour tissuesHead and neck cancer (HNC)FMISO Gagel et al [139]A correlation was reported between the tumour-to-muscle ratio (TMR), the uptake of FMISO PET and pO 2 polarography in 16 patients with HNC, indicating that FMISO-TMR is a suitable method for measuring tumour hypoxia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SUVmax correlated positively with HIF–1a immunostaining Beppu et al [123]Intratumoural pO2 measured using microelectrodes during tumour resection and HIFa immunostaining correlated with FRP-170 uptake in 12 patients with high-grade gliomas. The mean pO2 was significantly lower in the areas of high uptake than in those of low uptake, suggesting that high accumulation of FRP-170 might indicate viable hypoxic tissuesCu-ATSM Hino-Shishikura et al [225]Tumour hypoxia assessed by [ 62 Cu]Cu-ATSM PET/CT correlates with diffusion capacity obtained by diffusion weighted MRI imaging and may be useful for grading gliomas. [62Cu]Cu-ATSM uptake was significantly higher in high-grade gliomas than in normal or lower grade tumour tissuesHead and neck cancer (HNC)FMISO Gagel et al [139]A correlation was reported between the tumour-to-muscle ratio (TMR), the uptake of FMISO PET and pO 2 polarography in 16 patients with HNC, indicating that FMISO-TMR is a suitable method for measuring tumour hypoxia.…”
Section: Methodsmentioning
confidence: 99%
“…Disease-free survival correlates negatively with baseline tracer uptake and initial hypoxic volume Okamoto et al [235]Evaluated the reproducibility of FMISO uptake in HNC in 11 patients on two separate occasions 48 h apart. FMISO PET can identify hypoxic areas with high reproducibility, thus enabling accurate target delineation during radiotherapy planning Lee et al [252]Heterogeneous distribution of FMISO was seen in the primary and/or nodal disease in majority of the patients Jansen et al [225]Gadopentetate dimeglumine (Gd-DTPA)-based dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) was combined with FMISO PET in 13 node-positive HNC patients. FMISO uptake negatively correlated with tumour perfusion as assessed by DCE-MRI Abolmaali et al [145]FMISO contrast increases 2–4 h post injection Kikuchi et al [254]Disease-specific survival was significantly lower in patients with high baseline FMISO uptake Yamane et al [255]FMISO tumour uptake and hypoxic volume significantly decreased after neo-adjuvant chemotherapy in 13 patients with HNC Zips et al [247]Hypoxia PET imaging with FMISO after 1 or 2 weeks of radiotherapy correlated better with outcome than imaging pre-treatment Sato et al [146]HIF1 expression was strongly correlated with FMISO uptake, but not with FDG uptake, suggesting that FMISO uptake in the primary site of oral squamous cell carcinoma (SCC) indicates a hypoxic environment with HIF1 expression Tachibana et al [243]Showed that 9 of 10 patients with HNC had positive FMISO uptake before radiation therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports on the association between tissue hypoxia in different tumor entities and properties in DWI or corresponding ADC maps are inconsistent. Hino-Shishikura et al reported a negative correlation between ADC values and the SUV max and tumor-to-background ratios in brain tumors obtained with hypoxia-specific PET imaging 31 . Hompland et al demonstrated a weak negative correlation between ADC values and hypoxic fraction assessed by pimonidazole tissue staining in malignant melanoma xenografts.…”
Section: Patientmentioning
confidence: 99%
“…In another study, Hino-Shishikura et al demonstrated that tumor hypoxia, assessed by [ 62 Cu]ATSM-PET/CT, correlates with microscopic diffusion capacity, assessed by diffusion weighted imaging (DWI), in primary brain tumors. (50) DWI is a special MRI sequence that has been successfully used for imaging acute brain ischemia and apparent diffusion coefficients (ADC) derived from DWI have been used to grade primary brain tumors. (51, 52) Patients with low-grade glioma, glioblastoma (GBM) and primary central nervous system lymphoma were studied; high [ 62 Cu]ATSM uptake and high DWI signal intensity were seen in GBM and lymphoma whereas low [ 62 Cu]ATSM uptake and low DWI signal intensity were seen in low-grade gliomas.…”
Section: Clinical Oncologymentioning
confidence: 99%